Exterior material for power storage device
By adding mixed particles of different particle sizes and lubricant to the inner surface of the heat-fused layer, the problem of unstable sliding and formability of the outer casing material for energy storage devices in the prior art is solved, and stable and good formability and sliding properties are achieved.
Patent Information
- Application Number
- CN202480025952.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-04-17
- Filing Date
- 2024-04-16
- Publication Date
- 2025-11-14
AI Technical Summary
Existing battery storage device casing materials have unstable sliding and formability during molding, especially when molding at near right angles, they are prone to delamination, and variations in the amount of lubricant can lead to deviations in sliding performance.
Mixed particles of different sizes, including small, medium and large particles, are added to the inner surface of the heat-fused layer to form a sealing layer with a specific particle size distribution and thickness, combined with a lubricant to improve sliding and formability.
By combining particle distribution and lubricant, the sliding and formability of the hot-melt layer are improved, ensuring the stability and reliability of the energy storage device.
Smart Images

Figure CN120958642A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to batteries and capacitors used in mobile devices such as smartphones and tablets, and to external materials for batteries and capacitors used in energy storage devices such as hybrid vehicles, electric vehicles, wind power generation, solar power generation, and nighttime electricity storage. Background Technology
[0002] In recent years, with the trend towards thinner and lighter mobile devices such as smartphones and tablets, the outer casing materials for energy storage devices such as lithium-ion secondary batteries, lithium polymer secondary batteries, lithium-ion capacitors, and double-layer capacitors have replaced traditional metal cans with laminates consisting of a heat-resistant resin layer (substrate layer), an adhesive layer, a metal foil layer (barrier layer), an adhesive layer, and a thermoplastic resin layer (thermoplastic bonding layer). Furthermore, there is an increasing trend of using these laminates (outer casing materials) to encapsulate power supplies for electric vehicles, large power supplies for energy storage, and capacitors. When forming the outer casing material for energy storage devices, the aforementioned laminate is cold-formed into a roughly rectangular or other three-dimensional shape through processes such as embossing and deep drawing. This three-dimensional shape ensures sufficient storage space for the main body of the energy storage device. Therefore, to ensure precise storage space, improved formability is preferable.
[0003] For example, the outer casing material for the energy storage device shown in Patent Document 1 below improves sliding properties by adding lubricant to the exposed surface of the inner layer (thermal fusion layer), thereby ensuring good formability.
[0004] Furthermore, the outer casing material for the energy storage device shown in Patent Document 2 below ensures good formability by causing phase separation on the exposed surface of the heat-fused layer or by adding fine particles to the exposed layer, thereby appropriately adjusting the centerline average roughness (Ra).
[0005] Existing technical documents Patent documents Patent Document 1: Japanese Patent No. 3774163 Patent Document 2: Japanese Patent No. 5380762 Summary of the Invention
[0006] The problem that the invention aims to solve However, in the conventional battery casing material shown in Patent Document 1, there is a problem as follows: the exposed layer with added lubricant is an easily transferable surface layer, so the amount of lubricant present changes during use, resulting in deviations in sliding properties and making it impossible to obtain stable and good formability. In addition, when molding at an angle close to a right angle, such as the concave corner of the molding part, delamination is prone to occur, which also makes it difficult to obtain good formability.
[0007] Furthermore, in the conventional outer casing material for energy storage devices shown in Patent Document 2, there is a problem that: unevenness and other irregularities are required over a wide range of exposed surfaces, but although the sliding performance is partially improved by adjusting the average roughness (Ra) of the centerline, it is not possible to obtain sliding performance without deviation over the entire area, and it is not possible to obtain stable and good formability.
[0008] The preferred embodiments of the present invention are proposed in view of the above and / or other problems in the related art. The preferred embodiments of the present invention can significantly improve existing methods and / or apparatuses.
[0009] The present invention was made in view of the above-mentioned problems, and its object is to provide an outer casing material for an energy storage device that can achieve stable and good formability.
[0010] Other objects and advantages of the present invention will become apparent from the following preferred embodiments.
[0011] Methods for solving problems To address the aforementioned issues, the present invention provides the following means.
[0012] [1] An external casing material for an energy storage device, comprising a metal foil layer, a resin-based substrate layer disposed on the outer surface of the metal foil layer, and a thermoplastic resin heat-fusion layer disposed on the inner surface of the aforementioned metal foil layer, characterized in that, The sealing layer disposed on the innermost surface side of the aforementioned thermal fusion layer contains at least two mixed particles with different volume average particle sizes, which constitute the D50 of the cumulative distribution of particles, as determined by particle size distribution measurement based on laser diffraction scattering. In the aforementioned cumulative distribution of mixed particles, counting starting from the smallest particle size, the D10 of the 10% of particle sizes in the cumulative distribution is less than 2 μm, and the D90 of the 90% of particle sizes in the cumulative distribution is greater than 6 μm. In the aforementioned particle size distribution of the mixed particles, only one peak is present in the range of D10 to D90. The peak values in the particle size distribution of the aforementioned mixed particles are 1 μm to 10 μm.
[0013] [2] The external material for the energy storage device as described in item 1 above, wherein the aforementioned mixed particles include incompatible particles with three different distributions of volume average particle size, namely small particles, medium particles and large particles. The volume average particle size of the aforementioned small particles is 0.05 μm to 5 μm. The volume average particle size of the aforementioned particles is 3 μm to 8 μm. The volume average particle size of the aforementioned large particles is 7–15 μm.
[0014] [3] The external material for the energy storage device as described in item 1 or 2 above, wherein the weight content of the aforementioned mixed particles in the aforementioned sealing layer is 3000ppm to 20000ppm.
[0015] [4] The external material for the energy storage device as described in any one of the preceding items 1 to 3, wherein the thickness of the aforementioned sealing layer is 5 μm or more.
[0016] [5] The external material for the energy storage device as described in any one of paragraphs 1 to 4 above, wherein the aspect ratio of the aforementioned mixed particles is 0.2 to 1.
[0017] [6] The external material for the energy storage device as described in any one of the preceding items 1 to 5, wherein the aforementioned sealing layer contains a lubricant.
[0018] [7] The external material for the energy storage device as described in any one of the preceding items 1 to 6 shall satisfy the relationship (D90-D10) / D50=0.5 to 5.
[0019] [8] A film for the heat-fusion bonding layer of an outer casing material for an energy storage device, wherein the film is the same as that used in the heat-fusion bonding layer of the outer casing material for an energy storage device as described in any one of items 1 to 7 above, characterized in that... The portion equivalent to the aforementioned sealing layer is composed of a resin layer containing the aforementioned mixed particles.
[0020] [9] A method for manufacturing a film for a heat-fusion bonding layer in an outer casing material for an energy storage device, characterized in that, The portion corresponding to the aforementioned sealing layer is formed by a resin layer containing the aforementioned mixed particles.
[0021]
[10] An energy storage device, characterized in that the energy storage device comprises: The main body of the energy storage device; and The outer casing material as described in any one of claims 1 to 7, The main body of the aforementioned energy storage device is externally packaged using the aforementioned external materials.
[0022] Invention Effects According to the invention [1], the outer material for the storage device contains mixed particles of different sizes added to the sealing layer on the inner surface side of the heat-fusion layer, thus forming protrusions of different sizes. The mixed particles can be measured as particles with a certain particle size distribution width and a peak within the conditions in the particle size distribution measurement results. Therefore, it is not easy for the mixed particles to aggregate. The particles can be dispersed one by one and without bias on the inner surface of the heat-fusion layer, which can reduce the contact area with the mold and other molding fixtures during molding, thereby improving the sliding properties and obtaining stable and good molding properties.
[0023] According to the invention [2], the outer casing material for the energy storage device contains small, medium and large particles with specific particle sizes in the sealing layer, so it is easy to combine with mixed particles with the desired particle size distribution, and can form the target unevenness on the inner surface of the heat-welded layer, which can further reduce the contact area with the molding jig during molding, thereby further improving the moldability.
[0024] According to the invention [3], the outer material for the energy storage device has a specific content of mixed particles in the sealing layer, so that the mixed particles can be appropriately dispersed in the sealing layer and configured in a good balance, and the desired unevenness can be formed on the inner surface of the heat-welded layer, thereby further improving the formability.
[0025] According to the invention [4], the outer casing material for the energy storage device has a specific thickness of the sealing layer, so the mixed particles can be firmly fixed to the sealing layer in a stable state, and the mixed particles can be prevented from falling off and other adverse conditions, thereby further improving the moldability.
[0026] According to the invention [5], the outer casing material for the energy storage device has a specific aspect ratio of the mixed particles, so that no matter which direction the mixed particles are tilted, the protrusion can be fully formed and it is not easy to fall off, which can further improve the formability.
[0027] According to the invention [6], the outer casing material for the energy storage device contains a lubricating material in the sealing layer. Therefore, when a certain temperature is reached, the lubricating material is released and exposed on the inner surface of the heat-fused layer, which can further improve the sliding properties and thus further improve the formability.
[0028] According to the invention [7], the outer material for the energy storage device satisfies the relationship (D90-D10) / D50=0.5~5, thus enabling the volume distribution of the mixed particles to become a wide distribution more reliably, and further improving the formability during molding.
[0029] The heat-fusion bonding layer film for the outer casing material of the energy storage device according to the invention [8] can be used to reliably manufacture the outer casing material of the invention described above.
[0030] According to the manufacturing method of the heat-fusion layer film of the outer material for the storage device according to the invention [9], the outer material of the invention can be reliably manufactured.
[0031] According to the invention
[10] , since the aforementioned outer material has excellent sliding properties with the molding fixture, it is possible to provide a high-quality energy storage device with high operational reliability. Attached Figure Description
[0032] [ Figure 1 ] Figure 1 This is a cross-sectional view showing the outer casing material of an energy storage device as an embodiment of the present invention.
[0033] [ Figure 2 ] Figure 2 This is a schematic cross-sectional view of the heat-fusion layer of the outer casing material for the energy storage device used to illustrate the implementation method.
[0034] [ Figure 3 ] Figure 3 It is a diagram showing the particle size distribution of each particle and the overall mixture of particles in the embodiment.
[0035] [ Figure 4 ] Figure 4 This is a graph showing the particle size distribution and cumulative distribution of the mixed particles in the embodiment.
[0036] [ Figure 5 ] Figure 5 This is a graph used to illustrate the peak values in the particle size distribution of the mixed particles in the implementation method.
[0037] [ Figure 6 ] Figure 6 This is a schematic cross-sectional view of a sealing layer in which lubricant is deposited in the heat-fusion layer used to illustrate the implementation method.
[0038] [ Figure 7 ] Figure 7 This is a cross-sectional view showing an energy storage device made of the outer casing material used in the embodiment.
[0039] [ Figure 8 ] Figure 8 This is a perspective view showing the energy storage device of the embodiment exploded. Detailed Implementation
[0040] Figure 1This is a cross-sectional view showing the outer casing material for an energy storage device according to an embodiment of the present invention. As shown in the figure, the outer casing material 1 for the energy storage device includes a metal foil layer 4 made of metal foil, a heat-resistant resin substrate layer 2 disposed on the outer surface side of the metal foil layer 4 and serving as an outer layer, an adhesive layer 5 disposed on the inner surface side of the metal foil layer 4, and a heat-fusion layer (sealant layer) 3 made of heat-fusion resin disposed on the inner surface side of the adhesive layer 5 and serving as an inner layer.
[0041] It should be noted that in this specification, the direction ( Figure 1 In describing the positions of the layers constituting the battery packaging material (in the upward direction), the direction of the substrate layer 2 is referred to as the outer side, and the direction of the heat-fusion layer 3 is referred to as the outer side. Figure 1 The downward direction is called the inner side.
[0042] The substrate layer 2 is preferably made of polyamide resin, polyester resin, polyolefin resin, polyimide resin, etc., and can be formed by coating a film or membrane. The substrate layer 2 is particularly preferably made of a biaxially stretched film of the aforementioned resin, wherein biaxially stretched polyamide film or biaxially stretched polyester film is preferred. Among these, there are no particular limitations on the biaxially stretched polyamide film; biaxially stretched 6 nylon film, biaxially stretched 6,6 nylon film, biaxially stretched MXD nylon film, etc., can be used appropriately. As for the polyester film, biaxially stretched polybutylene terephthalate (PBT) film, biaxially stretched polyethylene terephthalate (PET) film, biaxially stretched polyethylene naphthalate (PEN) film, etc., can be used appropriately.
[0043] Furthermore, as the heat-resistant resin constituting the substrate layer 2, it is preferable to use a thermoplastic resin with a melting point of 10°C or higher than that of the thermoplastic resin constituting the heat-fusion layer 3, and more preferably a thermoplastic resin with a melting point of 20°C or higher. The thickness of the substrate layer 2 is preferably set to 9 μm to 50 μm.
[0044] The metal foil layer 4 can be a cladding material made by laminating two or more metals, such as aluminum (Al), copper (Cu), stainless steel (SUS), titanium (Ti), or nickel (Ni) foil, using individual metal foils. The thickness of the metal foil layer 4 is preferably set between 20 μm and 150 μm. That is, if the thickness is too thin, pinholes may occur, leading to reduced durability; conversely, if the thickness is too thick, it may reduce formability.
[0045] Preferably, a base layer is formed on at least one side of the inner and outer surfaces of the metal foil layer 4, particularly on the side of the heat-fusion layer 3 (inner surface).
[0046] The substrate layer can be formed through chemical conversion treatments such as coating with silane coupling agents or chromate treatment. A substrate layer thickness of 0.01 μm to 1 μm is preferred.
[0047] By forming the base layer in this way, the corrosion resistance of the metal foil layer 4 can be improved, and the bonding strength with the adhesive layer 5 disposed on the inner surface can be increased, effectively preventing the adhesive layer 5 from peeling off.
[0048] When the base layer is formed by a coating obtained by chemical conversion treatment (chemical conversion treatment coating), the chemical conversion treatment coating is sometimes selected by combination with the adhesive layer 5, but for example, a coating obtained by chromic acid treatment, a coating obtained by chromate phosphate treatment, a coating obtained by zinc phosphate treatment, a coating obtained by non-chromate treatment using zirconium and titanium as metal components to replace Cr, or an oxide coating obtained by boehmite treatment can be used.
[0049] As needed, the substrate layer 2 is laminated together on the outer surface of the metal foil layer 4 by means of an adhesive.
[0050] As an adhesive for bonding the substrate layer 2 to the metal foil layer 4, and as an inter-film adhesive when the substrate layer 2 is formed from a multilayer film, an adhesive layer formed by a two-component curing adhesive can be appropriately used. For example, a two-component curing adhesive consisting of a first liquid (main agent) and a second liquid (curing agent) can be used, wherein the first liquid (main agent) contains one or more polyols selected from the group consisting of polyurethane polyols, polyester polyols, polyether polyols, and polyester urethane polyols, and the second liquid (curing agent) contains isocyanate. The thickness of this adhesive is preferably set to 2 μm to 5 μm.
[0051] As the adhesive layer 5 disposed on the inner surface of the metal foil layer 4, adhesives comprising one or more polyurethane-based resins, acrylic resins, epoxy resins, polyolefin resins, elastic resins, fluorinated resins, acid-modified polypropylene resins, etc., can be suitably used. Among these, adhesives comprising polyurethane composite resins with acid-modified polyolefins as the main agent are particularly preferred. The thickness of the adhesive layer 5 is preferably set to 2 μm to 5 μm.
[0052] It should be noted that adhesive layer 5 can also be formed by thermal lamination of a modified polyolefin (e.g., acid-modified polypropylene). In this case, the preferred thickness is 10 μm to 30 μm.
[0053] Examples of thermoplastic resins constituting the heat-fusion bonding layer 3 include polyethylene resins such as LDPE (low-density polyethylene), LLDPE (linear low-density polyethylene), HDPE (high-density polyethylene), and polyethylene copolymers; polypropylene resins such as rPP (random polypropylene), bPP (block polypropylene), hPP (homogeneous polypropylene), and polypropylene copolymers; polybutene copolymers; and ionomers. Among these, polypropylene resins are suitable for use considering electrolyte resistance, water resistance, and oxygen barrier properties. Furthermore, from an operational point of view, a film-like form is preferred, and unstretched polypropylene films such as CPP (cast polypropylene) and IPP (blown polypropylene) are particularly preferred.
[0054] Figure 2 This is a cross-sectional view showing the heat-fusion layer 3 in the outer casing material 1 of this embodiment. (See diagram below.) Figure 1 and Figure 2 As shown, in this embodiment, the heat-fusion layer 3 is a laminate of three layers: a sealing layer 31 disposed on the innermost surface side, an outer layer 33 disposed on the outermost surface side, also known as a metal foil side layer, a laminate, etc., and an intermediate layer 32 disposed between the sealing layer 31 and the outer layer 33.
[0055] It should be noted that in this invention, the heat-fusion layer 3 is not limited to three layers; it can be a single layer, two layers, or four or more layers. However, in this invention, when the heat-fusion layer 3 is a multilayer structure, it is easier to form the desired multilayer structure by using multiple layers.
[0056] In addition, in this invention, it is not necessary to change the resin in each layer. For example, the resin of the innermost layer with added mixed particles and the resin of the adjacent layer without added mixed particles can be the same resin to form the sealing layer 31, the intermediate layer 32, and the outer layer 33.
[0057] As shown above, the film used for the heat-sealing layer 3 can be a single layer or multiple layers, but considering heat-sealing performance, delamination resistance, and insulation, it is preferable to form a multilayer film obtained by co-extrusion or the like. For example, in this embodiment, a three-layer co-extruded CPP film obtained by distributing rPP layers on both sides of an hPP layer or a bPP layer can be used. In the heat-sealing layer 3 obtained from this three-layer co-extruded CPP film, the middle hPP layer or bPP layer is configured as an intermediate layer 32, one of the two sides (inner and outer surfaces) of the rPP layer is configured as a sealing layer 31, and the other rPP layer is configured as an outer layer 33.
[0058] In this embodiment, the overall thickness of the heat-fusion layer 3 is preferably set to 20 μm to 120 μm. Furthermore, the thickness of the sealing layer 31 is preferably set to 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more. That is, by specifying the thickness of the sealing layer 31 within this range, the mixed particles (described later) contained in the sealing layer 31 can be reliably maintained in a stable state within the sealing layer, reliably preventing adverse conditions such as the mixed particles falling off.
[0059] In this embodiment, the sealing layer 31 contains three incompatible particles, namely, three incompatible particles M1 to M3, which are mixed particles.
[0060] As the mixed particles M1 to M3, metal oxides, resin beads, etc., can be used. Specific examples include silica, alumina, calcium carbonate, barium carbonate, titanium dioxide, aluminum silicate, talc, kaolin, acrylic resin beads, polyethylene resin beads, and polyethylene elastomer. It should be noted that the composition of particles M1 to M3 is preferably a combination of two or more of the aforementioned particles to form the mixed particles. By using particles with two or more different compositions, aggregation of the mixed particles caused by van der Waals forces is less likely to occur, and the mixed particles can be dispersed within the sealing layer 31 to form a suitable unevenness.
[0061] Relative to the sealing layer 31, the content of mixed particles M1 to M3, by weight, is preferably set to 3000 ppm to 20000 ppm, and more preferably 7000 ppm to 18000 ppm. That is, when the content of mixed particles M1 to M3 is set within this range, the mixed particles M1 to M3 can be appropriately dispersed within the sealing layer 31 and uniformly arranged, and the desired unevenness can be formed on the inner surface of the heat-welding layer 3.
[0062] In this embodiment, the mixed particles (incompatible particles) contained in the sealing layer 31 are composed of three types of particles with different cumulative distribution 50% particle size D50, i.e., volume average particle size (median particle size), namely small particles M1, medium particles M2 and large particles M3.
[0063] A sealing layer 31 containing small particles M1, medium particles M2, and large particles M3 of different sizes is formed by a portion of each particle M1 to M3 extending from the inner surface of the resin component such as rPP. Figure 1 and Figure 2 The sealing layer 31 is configured to protrude inward (towards the bottom of the figure) from the lower side, and the inner surface of the sealing layer 31 has irregularities.
[0064] As the small particles M1, it is preferable to use particles with a volume average particle diameter (D50) of 0.05 μm to 5 μm, and more preferably to use particles with a diameter of 0.5 μm to 3 μm.
[0065] As the medium particles M2, it is preferable to use particles with a volume average particle diameter (D50) of 3 μm to 8 μm, and more preferably to use particles with a diameter of 4 μm to 7 μm.
[0066] As the large particles M3, it is preferable to use particles with a volume average particle diameter (D50) of 7 μm to 15 μm, and more preferably to use particles with a diameter of 8 μm to 13 μm.
[0067] In the present embodiment, since the sealing layer 31 contains three types of particles M1 to M3 with different D50 particle diameters, the small particles M1 and the large particles M3 are used to widen the particle size distribution, and the medium particles M2 are used to integrate them into one distribution. As a result, the particles of each size can be dispersed as a whole, which helps to form protrusions of various sizes without uneven distribution. When molding the exterior material 1, the contact area with the mold such as a molding jig can be reduced, thereby improving the sliding property and obtaining stable and good moldability.
[0068] It should be noted that when particles of the same size are mixed instead of mixing particles of different sizes, the sizes of the protrusions are homogenized, so the surface shape becomes monotonous, which may lead to a decrease in the sliding property and moldability, and printing (Japanese: type attachment) of the exterior material 1 caused by the protrusions.
[0069] In addition, in the present embodiment, by using the small particles M1, fine irregularities can be formed on the surface (inner surface) of the heat fusion bonding layer 3, so that when molding the exterior material 1, the adhesion to the mold can be suppressed.
[0070] In addition, by using the large particles M3, protrusions can be reliably formed on the inner surface of the heat fusion bonding layer 3, so that when molding the exterior material 1, the dynamic frictional force with the mold can be reduced.
[0071] In addition, by using the medium particles M2, small protrusions can be formed on the inner surface of the heat fusion bonding layer 3, and the uneven distribution of the protrusions can be prevented, so that the effects brought by the small particles M1 and the large particles M3 can be further improved.
[0072] In addition, in the present embodiment, by specifying the particle diameters (D50) of the respective particles M1 to M3 within the above ranges, it is possible to easily mix mixed particles having a desired particle size distribution, and to form target irregularities on the inner surface of the heat fusion bonding layer 3. When molding the exterior material 1, etc., the contact area with the mold can be further reduced, thereby further improving the moldability.
[0073] Furthermore, in this embodiment, when the content of the mixed particles is specified within the above-mentioned range, or when the thickness of the sealing layer 31 is specified within the above-mentioned range, it is possible to prevent each particle from falling off the sealing layer 31, and the effect brought by the protrusion can be fully utilized, thereby obtaining good formability more reliably.
[0074] In this embodiment, the weight ratio (of large particles M3: medium particles M2: small particles M1) is preferably adjusted to 0.5–1.5:1–3:0.5–1.5, and more preferably to 0.8–1.2:1.5–2.5:0.8–1.2. That is, by adjusting the weight ratio to this range, the aforementioned effects resulting from the combination of particles M1 to M3 can be obtained more reliably.
[0075] Figure 3 This diagram illustrates the individual particle size distributions of small particles M1, medium particles M2, and large particles M3 in this embodiment, as well as the particle size distribution of the mixed particles obtained by mixing small particles M1, medium particles M2, and large particles M3. As shown in the diagram, compared to large particles M3, small particles M1 and medium particles M2 have smaller particle sizes. Therefore, when mixed with the same amount (weight and volume) as large particles M3, the amount of particles present in the particle size distribution, i.e., the number of particles, becomes larger.
[0076] In this invention, the particle size distribution and cumulative distribution are determined based on laser diffraction (laser diffraction scattering method).
[0077] It should be noted that in this embodiment, the example given is the use of three types of particles M1 to M3 with different volume average particle sizes (D50). However, this is not the only limitation. As long as the mixed particles meet the conditions in the particle size distribution, in this invention, at least two types of particles with different volume average particle sizes (D50) can be used as mixed particles. For example, small particles M1 and medium particles M2 can be used as mixed particles, or small particles M1 and large particles M3 can be used as mixed particles. Furthermore, four or more types of particles with different volume average particle sizes (D50) can be used to form mixed particles.
[0078] Figure 4 This is a graph showing the particle size distribution and cumulative distribution of the mixed particles in this embodiment. As shown in the graph, in the particle size distribution of the mixed particles, starting from the smaller particle size, there is only one peak (mountain) in the cumulative distribution range of 10% particle size (D10) to 90% particle size (D90), and there are no more than two peaks in this range.
[0079] Here, for the purposes of this invention, in the particle size distribution of the mixed particles, only one peak is contained in the range of D10 to D90. Even if peaks exist outside the range of D10 to D90, peaks outside this range are irrelevant to this invention. For example, in Figure 5 In the particle size distribution, there is a peak at a position smaller than D10, but this peak is not counted in this invention. That is, the particle size distribution in this figure contains only one peak in the range of D10 to D90, which is the subject of this invention.
[0080] Furthermore, in this embodiment, in the cumulative distribution of the mixed particles, the particle size of D10 is 2 μm or more, and the particle size of D90 is 6 μm or more. Additionally, in this embodiment, the mode diameter, which serves as the peak value in the particle size distribution of the mixed particles, is 1 μm to 10 μm.
[0081] In this embodiment, since the particle size and mode diameter of D10 and D90 are specified to the aforementioned values, the mixed particles can be distributed in a wide, non-sharp manner. On the inner surface of the heat-fused layer 3, the protrusions formed by particles M1 to M3 can be uniformly dispersed without bias. Therefore, during the molding of the outer material 1, stress concentration on the mold is less likely to occur, thus improving sliding properties and further enhancing moldability.
[0082] In this embodiment, it is preferable to satisfy the relationship (D90-D10) / D50 = 0.5 to 5, and more preferably, it is preferable to satisfy the relationship (D90-D10) / D50 = 1.5 to 3. That is, when this relationship is satisfied, the volume distribution of the mixed particles as a whole can be reliably made to be a wide distribution, and various sizes of unevenness can be set, thus further improving the formability of the outer material 1 during molding.
[0083] Furthermore, in this embodiment, the particles M1 to M3 constituting the mixed particles are preferably particles with an aspect ratio (minor diameter / major diameter) of 0.2 to 1. That is, in this case, the particles form a certain block shape, so no matter which direction the particles M1 to M3 are tilted, the protrusions can be formed sufficiently and they are not easy to fall off. When molding the outer material 1, the formability can be further improved reliably.
[0084] In this embodiment, it is preferable that the sealing layer 31 of the heat-fusion layer 3 contains a lubricant.
[0085] Examples of such lubricants include saturated fatty acid amides, unsaturated fatty acid amides, substituted amides, hydroxymethyl amides, saturated fatty acid diamides, unsaturated fatty acid diamides, fatty acid ester amides, and aromatic diamides.
[0086] Specifically, examples of saturated fatty acid amides include lauryl amide, palmitamide, stearamide, behenamide, and hydroxystearamide.
[0087] Furthermore, examples of unsaturated fatty acid amides include oleamide and erucamide.
[0088] Furthermore, examples of substituted amides include N-oleopalmitoamide, N-stearostearoamide, N-stearooleoamide, N-oleostearoamide, and N-stearoerucamide.
[0089] Furthermore, examples of hydroxymethyl amides include hydroxymethyl stearamide and the like.
[0090] Furthermore, examples of saturated fatty acid diamides include methylene bis-stearamide, ethylene bis-decanoic acid amide, ethylene bis-lauric acid amide, ethylene bis-stearamide, ethylene bis-hydroxystearamide, ethylene bis-benzylamine, hexamethylene bis-stearamide, hexamethylene bis-benzylamine, hexamethylene hydroxystearamide, N,N'-distearate adipamide, and N,N'-distearate sebacic acid amide.
[0091] Furthermore, examples of unsaturated fatty acid diamides include ethylene dioleoamide, ethylene dierucamide, hexamethylene dioleoamide, N,N'-dioleoyl adipamide, and N,N'-dioleoyl sebacate amide.
[0092] Furthermore, as a fatty acid ester amide, stearamide ethyl stearate can be exemplified.
[0093] Examples of aromatic diamides include m-xylene-distearamide, m-xylene-dihydroxystearamide, and N,N'-distearyl isophthalamide.
[0094] The amount of lubricant deposited on the inner surface of the heat-fusion layer 3 is preferably adjusted to 0.1 μg / cm. 2 ~1μg / cm 2 (Contains 0.1 μg / cm) 2 and 1μg / cm 2 If the amount of lubricant released is too small, good lubrication may not be achieved, which is not preferable. Conversely, if the amount of lubricant released is too large, the frequency of lubricant-related white powder, equipment contamination, etc., may increase, which is also not preferable.
[0095] It should be noted that, as Figure 6As shown, the inner surface of the heat-fusion layer 3 is formed into an uneven structure by particles M1 to M3, which can suppress the excessive precipitation of lubricant on the inner surface of the heat-fusion layer 3. When the specified temperature is reached, an appropriate amount of lubricant is precipitated. By using the lubricant layer 6 formed by this lubricant to cover the inner surface of the heat-fusion layer 3, the sliding performance for the forming fixture can be further improved.
[0096] Furthermore, when the outer material 1 of this embodiment is wound into a roller shape, for example, by making the heat-fused layer 3 contact the outermost layer such as the substrate layer 2, the position of the protrusion obtained by each particle M1 to M3 preferentially contacts other parts (such as the substrate layer 2), thus suppressing the amount of lubricant transferred to other parts.
[0097] It should be noted that, in this invention, to further improve the sliding properties during molding, a substrate protective layer formed of an adhesive resin containing microparticles may be provided on the outer side of the substrate layer 2. As the microparticles, incompatible particles used as the mixed particles described above in this embodiment may be used, and as the adhesive resin, urethane resins, acrylic resins, urethane acrylate resins, fluorinated resins, etc., may be used.
[0098] The outer casing material 1 of the energy storage device constructed as described above is directly in sheet form, or formed into a specified shape as required by thermoforming such as deep drawing or bulging, and is used as the outer casing of the energy storage device.
[0099] For example, Figure 7 and Figure 8 These are cross-sectional and exploded perspective views showing the energy storage device 30 manufactured using the outer casing material 1 of this embodiment. As shown in both figures, the energy storage device 30 is a lithium-ion secondary battery. In this embodiment, the outer casing 15 is constructed by forming a tray member 14 obtained by molding the outer casing material 1 and a cover member 10 made of the planar (sheet-like) outer casing material 1. Then, a generally cuboid-shaped energy storage device main body (electrochemical element, etc.) 35 is housed in the receiving recess of the tray member 14 obtained by molding the outer casing material 1 of the present invention. The cover member 10 (outer casing material 1) of the present invention is arranged on the energy storage device main body 35 with its heat-welded layer 3 side as the inner (lower) side. The outer periphery of the heat-welded layer 3 of the cover member 10 is sealed to the heat-welded layer 3 of the flange portion (sealing periphery portion) 29 of the tray member 14 by heat sealing, thereby constructing the energy storage device 30. It should be noted that the inner surface of the receiving recess of the tray component 14 becomes the heat-fusion layer 3, and the outer surface of the receiving recess becomes the substrate layer 2.
[0100] exist Figure 7In the attached drawing, reference numeral "39" refers to the heat-sealed portion formed by joining (welding) the outer periphery of the cover component 10 with the flange portion (sealing periphery) 29 of the tray component 14. It should be noted that in the energy storage device 30, the front end of the electrode tab connected to the main body 35 of the energy storage device extends to the outside of the outer casing 15, but it is omitted from the drawing.
[0101] The energy storage device 30 made using the outer casing material 1 of this embodiment has excellent sliding properties to the molding die and high bonding strength between the heat-melting layer 3 and the adhesive layer 5. Therefore, it is possible to reliably provide an energy storage device product with high operational reliability and high quality.
[0102] The main body 35 of the energy storage device is not particularly limited, and examples include the main body of a battery, the main body of a capacitor, and the main body of a capacitor.
[0103] It should be noted that in the above embodiments, the outer casing 15 is composed of a tray component 14 obtained by molding the outer casing material 1 and a planar cover component 10. However, this combination is not particularly limited in the present invention. For example, the outer casing 15 may also be composed of a pair of planar (sheet-like) outer casing materials 1, or it may be composed of a pair of tray components 14 overlapping in an opposing state.
[0104] Example [Table 1] [Table 2] 1. Fabrication of film for heat-fusion bonding layer <Example 1> As shown in Tables 1 and 2, the film used for the heat-fusion bonding layer 3 in Example 1 of the outer casing material 1 for the energy storage device is described. That is, the film for the heat-fusion bonding layer 3 is a CPP film made by laminating a 16 μm thick rPP for the sealing layer, a 48 μm thick bPP for the intermediate layer, and a 16 μm thick rPP for the outer layer using a three-layer co-extrusion process with a T-die.
[0105] In the heat-fusion bonding layer film of this embodiment 1, in the sealing layer 31, 3000ppm of silica particles with an average particle size of 1.5μm are added as small particles M1, 6000ppm of silica particles with an average particle size of 6μm are added as medium particles M2, and 3000ppm of HDPE (high-density polyethylene) particles with an average particle size of 12μm are added as large particles M3.
[0106] As shown in Table 2, among the mixed particles M1 to M3 added to the sealing layer 31, the 10% particle size (D10) is 0.8 μm, the 50% particle size (D50) is 3.8 μm, the 90% particle size is 8.2 μm, the (D90-D10) / D50 ratio is 1.9, the aspect ratio is 0.8, the number of peaks in the volume distribution range of D10 to D90 is 1, and the peak position is 4.1 μm.
[0107] It should be noted that the particle size distribution of the mixed particles was determined using laser diffraction. Specifically, a Microtrac MT3000II was used as the instrument, and the measurement conditions were as follows: measurement range 0.02 μm-2000 μm, measurement time 30 seconds, 2 measurements, solvent methanol (refractive index 1.33), and particle setting for non-spherical particles (refractive index 1.54).
[0108] In addition, the aspect ratio of each particle was measured using a Sysmex FPIA-3000.
[0109] <Examples 2-17> The sealing layer resin, intermediate layer resin and outer layer resin shown in Tables 1 and 2 are laminated in the same manner as in Example 1 above to prepare the heat-fusion layer film of Examples 2 to 17.
[0110] <Examples 18, 19> Using the sealing layer resins shown in Tables 1 and 4, a single-layer unstretched film was made using a T-mold as the heat-fusion film for Examples 18 and 19.
[0111] <Comparative Examples 1-4> The sealing layer resin, intermediate layer resin, and outer layer resin shown in Tables 1 and 2 were laminated in the same manner as in Example 1 above to prepare a film for heat-fusion bonding. It should be noted that in the mixed particles of Comparative Example 1, there were two peaks in the volume distribution range of D10 to D90, and the positions of each peak were 1.9 μm and 9.3 μm.
[0112] 2. Fabrication of external materials for energy storage devices A chemical conversion coating was formed by coating both sides of a 40 μm thick aluminum foil (A8021-O) serving as the metal foil layer 4 with a chemical conversion treatment solution containing phosphoric acid, polyacrylic acid (acrylic resin), chromium (III) salt compound, water, and alcohol, followed by drying at 180°C. The chromium deposition of this chemical conversion coating was 10 mg / m² on each side. 2 .
[0113] Next, a 15 μm thick biaxially stretched 6 nylon (ONy) film, serving as substrate layer 2, is dry-laminated (bonded) onto one side (outer surface) of the aforementioned chemically converted aluminum foil (metal foil layer 4) using a 2-liquid curing urethane adhesive (3 μm).
[0114] Next, using a two-component curing adhesive (2 μm) of maleic acid-modified polypropylene resin and isocyanate, the outer surface of the outer layer of the CPP film for the heat-fusion layer prepared in the above examples and comparative examples is overlapped onto the other side (inner surface) of the aluminum foil (metal foil layer) after dry lamination. This is then sandwiched between a rubber roller and a lamination roller heated to 100°C for pressing, thereby performing dry lamination. Afterward, it is cured at 40°C for 10 days to obtain the outer packaging materials (laminated bodies) of the examples and comparative examples that serve as samples.
[0115] 3. Evaluation tests for each exterior material [Table 3] <Moldability Test> For the outer casing test pieces obtained by cutting the outer casing materials of the examples and comparative examples into specified sizes, a deep drawing die was used to increase the forming height (drawing depth) in 0.5mm increments within a range of 55mm in length and 35mm in width, and a deep drawing test was conducted. The indicated pressure under anti-wrinkle pressure during this forming was 0.475MPa, and the actual pressure (calculated value) was 0.7MPa.
[0116] Using transmitted light, it was visually confirmed whether pinholes had been generated at the corners of the deep-drawing recess during the forming process.
[0117] Furthermore, the presence of pinholes at a molding depth of 7 mm or more is evaluated as "◎", a molding depth of 6 mm or more but less than 7 mm is evaluated as "○", a molding depth of 5 mm or more but less than 6 μm is evaluated as "△", and a molding depth of less than 5 mm is evaluated as "×". In this evaluation, "◎", "○", and "△" are considered acceptable. The results are shown in Table 3.
[0118] <Laminate Strength (Sealing) Test> The exterior materials of the examples and comparative examples were cut into strips with a width of 15 mm, and the peel strength between the metal foil layer and the heat-sealing layer was measured in accordance with JIS K6854-3 (1999). When the peel strength was 4.0 N / 15 mm or more, it was evaluated as "◎"; when it was 3.0 N / 15 mm or more and less than 4.0 N / 15 mm, it was evaluated as "○"; when it was 2.0 N / 15 mm or more and less than 3.0 N / 15 mm, it was evaluated as "△"; when it was less than 2.0 N / 15 mm, it was evaluated as "×". In this evaluation, in this example, "◎", "○", and "△" were regarded as qualified. The results are shown in Table 3.
[0119] <Sliding property test (coefficient of kinetic friction)> The exterior materials of the examples and comparative examples were cut into a size of 80 mm × 200 mm, and the coefficient of kinetic friction was measured in accordance with JIS K 7125. The load weight (Japanese: ローセル重量) as the measurement condition was 100 N, and the weight of the counterweight was 200 g (including the weight of the sliding piece). The results of the coefficient of kinetic friction are shown in Table 3.
[0120] <Overall evaluation> As shown in Table 3, among the exterior materials of the examples, although the results had some deviations, all the examples received a satisfactory evaluation and reached the qualified level.
[0121] In contrast, among the exterior materials of Comparative Examples 1 to 4 that deviated from the gist of the present invention, any of the evaluations of formability, sealing property, and sliding property was poor.
[0122] This application claims the priority of Japanese Patent Application No. 2023-67332 filed on April 17, 2023, and the disclosure thereof directly constitutes a part of this application.
[0123] The terms and expressions used herein are for the purpose of explanation and are not used for restrictive interpretation, nor do they exclude any equivalents of the characteristic matters shown and described herein. It should be understood that various modifications within the scope of the claims of the present invention are also permitted.
[0124] Industrial applicability The exterior material for the power storage device of the present invention can be suitably used when manufacturing batteries and capacitors used in mobile devices such as smartphones and tablet terminals, and batteries and capacitors for power storage in hybrid vehicles, electric vehicles, wind power generation, solar power generation, and night power.
[0125] Explanation of reference numerals 1: Exterior material 2: Base material layer 3: Heat-sealing layer 30: Power storage device 31: Sealing layer 35: Main body of the device 4: Metal foil layer 6: Lubricant layer M1: Small particles M2: Medium particle M3: Large Particle
Claims
1. An external casing material for an energy storage device, comprising a metal foil layer, a resin-based substrate layer disposed on the outer surface of the metal foil layer, and a thermoplastic resin heat-fusion layer disposed on the inner surface of the metal foil layer, characterized in that, The sealing layer disposed on the innermost surface side of the thermal fusion layer contains at least two mixed particles with different volume average particle sizes, which constitute the D50 of the cumulative distribution of the particles, as determined by particle size distribution measurement based on laser diffraction scattering. In the cumulative distribution of the mixed particles, counting starting from the smallest particle size, the D10 of the 10% of particle sizes in the cumulative distribution is less than 2 μm, and the D90 of the 90% of particle sizes in the cumulative distribution is greater than 6 μm. In the particle size distribution of the mixed particles, only one peak is present in the range of D10 to D90. The peak value of the particle size distribution of the mixed particles is 1 μm to 10 μm.
2. The external casing material for the energy storage device as described in claim 1, wherein, The mixed particles comprise incompatible particles with three different volume-average particle sizes: small particles, medium particles, and large particles. The volume average particle size of the small particles is 0.05 μm to 5 μm. The volume average particle size of the particles is 3 μm to 8 μm. The volume average particle size of the large particles is 7–15 μm.
3. The external casing material for the energy storage device as described in claim 1 or 2, wherein, The weight content of the mixed particles in the sealing layer is 3000ppm to 20000ppm.
4. The external casing material for the energy storage device as described in any one of claims 1 to 3, wherein, The thickness of the sealing layer is 5 μm or more.
5. The external casing material for the energy storage device as described in any one of claims 1 to 4, wherein, The aspect ratio of the mixed particles is 0.2 to 1.
6. The external casing material for the energy storage device as described in any one of claims 1 to 5, wherein, The sealing layer contains a lubricant.
7. The external material for the energy storage device as described in any one of claims 1 to 6, which satisfies the relationship (D90-D10) / D50=0.5 to 5.
8. A film for the heat-fusion bonding layer of the outer casing material for an energy storage device, wherein the film is the same as that used in the heat-fusion bonding layer of the outer casing material for an energy storage device according to any one of claims 1 to 7, characterized in that, The portion corresponding to the sealing layer is composed of a resin layer containing the mixed particles.
9. A method for manufacturing a film for the heat-fusion bonding layer of an outer casing material for an energy storage device, comprising the method for manufacturing a film used in the heat-fusion bonding layer of an outer casing material for an energy storage device as described in any one of claims 1 to 7, characterized in that, The portion corresponding to the sealing layer is formed by a resin layer containing the mixed particles.
10. An energy storage device, characterized in that, The energy storage device includes: The main body of the energy storage device; and The outer casing material as described in any one of claims 1 to 7, The main body of the energy storage device is covered by the aforementioned external material.
Citation Information
Patent Citations
Method of treating waste water by activated sludge process
JP1978080762A
Ventilation device
JP2023067332A